Extended reach NRZ-OOK data transmission for 40G/60G/100G SWDM4 systems over multimode OM3/OM4 fibers - Agossou, Carlos M. M.; DJOGBE, LÉOPOLD; SANYA, MAX FREJUS O.; SOTINDJO, Patrick; VIANOU, Antoine; AUPETIT-BERTHELEMOT, Christelle (My University, 2022)
We propose by system simulation, an extension of transmission distances for shortwave wavelength division multiplexing applications such as 40G-SWDM4, 60G-SWDM4 and 100G-SWDM4 links over multimode (MMF) OM3 and OM4 fibers using vertical cavity surface emitting laser (VCSEL) as an optical source. This could be a solution for upgrading optical transmission systems in data centers. Non-return to zero - on off keying (NRZ-OOK) data is transmitted over 420 m of OM3 fiber and 655 m of OM4 fiber for 40G-SWDM4 applications, as well as 220 m of OM3 fiber and 340 m of OM4 fiber for 60G-SWDM4 applications, whereas for 100G-SWDM4 applications, this data is transmitted over 150 m of OM3 fiber and 225 m of OM4 fiber. Bit error rate curves as a function of the received optical power for all the wavelengths 850 nm, 880 nm, 910 nm and 940 nm used made it possible to demonstrate the impact of the modal bandwidth of these fibers on each of these wavelengths.
Keywords: LAN data center; MMF OM3/OM4; NRZ-OOK; SWDM; VCSEL